Analysis of Fatty Acid Composition of Thevetia peruviana and Hura crepitans Seed oils using GC-FID - K. A. Alabi; L. Lajide; B. J. Owolabi (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2013)
Fatty acids were extracted from Thevetia peruviana and Hura crepitans seed oils. The quantitative determination of fatty acid composition was carried out for each sample by methylation and application of gas chromatograph (GC-FID). The predominant fatty acids in the T. peruviana and H. crepitans are Palmitic acid (19.10% and 21.67%), Stearic acid (7.31% and 9.66%), Oleic acid (53.40% and 26.91%) and Linoleic acid (19.03% and 36.61%) respectively. In the two oils, the ratios of unsaturated fatty acid were very high about 73% for T. peruviana and 64% for H. crepitans which is an indication that both would be very good sources of oleochemicals for polymer and other industries.